The anatomy of mismatch in the college market - Tore Adam Reiremo (University of Oslo, Department of Economics, 2024)
Both the availability of college education and the demand for college skills have expanded rapidly over the past decades in most countries. However, it remains an open question whether the increasing number of college-educated workers are able to successfully match with jobs where college skills are rewarded. Using rich Norwegian administrative data, I provide evidence on the evolution of mismatch in the college market. I further decompose the overall college mismatch into (i) a structural mismatch that captures misalignment between underlying demand and supply, (ii) a geographical component, and (iii) a within-location assignment component. Over the past two decades, overall mismatch in the college market has remained relatively stable, affecting about 20% of workers, despite large shifts in both the demand and supply of college workers. I further show that within-location assignment mismatch can account for more than two-thirds of the overall mismatch and its relative contribution has remained relatively unchanged. This evidence points to the vital role of reassignment policies that improve matching in the college market.
Keywords: 330